Pembentukan Manhaj Jamaah Dalam Pengembangan Masyarakat Islam - Dianto, S.Sos.I., M.Kom.I, Icol (Jurnal at-Taghyir, 2019)
AbstractIslam as the religion of rahmatanlil'alamin means that Islam is universal and flexible to all aspects of life, including the life of mankind. Da'wah of Islam touches on the development of the resources of the Muslim community and the global community in humanizing humans, achieving a decent standard of living materially and immaterial (hasanah fid-dunya wal akhirat). However, the availability of potential natural resources has not been maximally utilized because of the low capacity and weak work ethic. Therefore, the establishment of Manhaj Jama'ah in development and empowerment activities is important to implement. Development that is centered on pilgrims can have a broader impact in efforts to build people's welfare and can build "peer networks" in community development activities.This paper is not an applicative study of a study but contains theoretical-academic exposures, which explain the efforts to develop Islamic society in congregation. In this article, it was explained the reason for the need for community development activities carried out in congregation, what strengths the pilgrims have and the stages of forming strong and independent jama'ah.Keywords: Manhaj, Jamaah, Community Development.Â AbstrakIslam sebagai agama rahmatanlilâ€™alamin bermakna bahwa Islam itu universal dan fleksibel terhadap semua aspek kehidupan makhluk, termasuk kehidupan umat manusia. Dakwah Islam menyentuh pembangunan sumber daya komunitas muslim dan masyarakat global dalam memanusiakan manusia, mencapai taraf hidup layak secara material dan immaterial (hasanah fid-dunya wal akhirat). Akan tetapi, ketersediaan potensi sumberdaya alam itu belum maksimal dimanfaatkan karena rendahnya kemampuan dan lemahnya etos kerja. Oleh karena itu, pembentukan manhaj jamaâ€™ah dalam kegiatan pengembangan dan pemberdayaan menjadi penting untuk dilaksanakan. Pengembangan yang dipusatkan pada jamaah dapat memberikan dampak yang lebih luas dalam upaya membangun kesejahteraan umat dan dapat membangun â€œjaringan sebayaâ€ dalam kegiatan pengembangan masyarakat.Paper ini bukanlah kajian aplikatif dari sebuah penelitian melainkan berisi paparan teoritis-akademis, yang menjelaskan upaya pengembangan masyarakat Islam itu dilakukan secara berjamaah. Dalam artikel ini dijelaskan alasan perlunya kegiatan pengembangan masyarakat itu dilakukan secara berjamaah, kekuatan apa yang dimiliki oleh jamaah dan tahapan membentuk jamaâ€™ah yang kuat dan mandiri.Kata Kunci: Manhaj, Jamaah, Pengembangan Masyarakat.